2013
DOI: 10.1016/j.jtcvs.2012.09.074
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a mitral valve replacement skills trainer: A simplified, low-cost approach

Abstract: Simulated mitral valve replacement can be performed using this simple, affordable, portable setup. Performance scores correlate with level of training and experience, but residents who performed 10 to 50 mitral valve replacements still failed to reach attending-level proficiency. This training simulator may facilitate skills practice and evaluation of competency in cardiac surgery trainees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…After the application of inclusion and exclusion criteria on the screening of titles and abstracts, 468 articles were excluded. Both screeners reviewed the remaining 32 articles at full text, and 18 articles were then excluded as follows: five were related to a noncardiac surgery specialty [27][28][29][30][31], four were conference proceedings [32][33][34][35], three were nontechnical skills simulation training [36][37][38], three used simulation to establish validity for the simulator [9,39,40] but no actual training, two had no trainee participation [41,42], and one met the inclusion criteria but was excluded because it had only self-reported confidence data [43]. After manual screening and search for citations, two additional articles were included [14,44].…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the application of inclusion and exclusion criteria on the screening of titles and abstracts, 468 articles were excluded. Both screeners reviewed the remaining 32 articles at full text, and 18 articles were then excluded as follows: five were related to a noncardiac surgery specialty [27][28][29][30][31], four were conference proceedings [32][33][34][35], three were nontechnical skills simulation training [36][37][38], three used simulation to establish validity for the simulator [9,39,40] but no actual training, two had no trainee participation [41,42], and one met the inclusion criteria but was excluded because it had only self-reported confidence data [43]. After manual screening and search for citations, two additional articles were included [14,44].…”
Section: Study Selectionmentioning
confidence: 99%
“…Cardiac surgery is a specialty that requires a high level of dexterity, and deliberative practice plays a significant role in skills mastery [5]. After the call for educational reform in cardiac surgery, many surgeons and training programs have sought to use the value of simulationbased skills training, and several simulators have been developed [6][7][8][9][10][11][12]. Training programs have concomitantly developed simulation curricula and boot camps to integrate simulation into the training process.…”
mentioning
confidence: 99%
“…We can consider broadening the field of participants in this competition to include all CT residents (integrated and traditional), general surgery residents, and perhaps medical students. Other affordable and accessible task simulators [16,17] are on the horizon, and one avenue is to integrate them into a multifaceted competition.…”
Section: Commentmentioning
confidence: 99%
“…Currently, several mitral valve surgery simulators and training models have been described to facilitate in this need. [11][12][13][14][15] Of these, only Verberkmoes and Verberkmoes-Broeders 12 reported the usability of their simulator for endoscopic minimally invasive mitral valve surgery (MIMVS). In addition, all of the aforementioned studies reported the use of low-fidelity simulators and/or models that can be seen as a black box without feedback.…”
Section: Perspectivementioning
confidence: 99%